2019
DOI: 10.1021/acsaem.9b02196
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Host Polymer Matrix for Self-Healing Luminescent Solar Concentrators

Abstract: Luminescent solar concentrators (LSCs) are a promising solar energy technology for reducing architectural barriers to the integration of photovoltaic systems into the built environment. In this work, the first demonstration of thin-film LSCs based on a thermally reversible cross-linked host polymer is presented. This smart material is obtained via a dynamic-chemistry approach based on the Diels−Alder (DA) reaction between a furan-functionalized acrylic copolymer and an aliphatic bismaleimide to obtain opticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…In the presence of a black absorbing background, a maximum ISC of 3.61 mA and a maximum output power of 0.86 mW were achieved, leading to a maximum ηdev,dark background of 0.24%. The lower overall device efficiencies of LR305-PDMS LSCs with respect to previously published LR305-based thin-film LSCs tested in analogous conditions (namely, in the presence of a black absorbing background and of a black mask in front of the LSC system, without employing any reflective element at the free edges of the waveguide) [15,83] could be attributed to the poor luminophore solubility of LR305 in PDMS host matrix. As documented in previous studies [68,71,72], dye aggregation issues are responsible for generating significant luminescence quenching, which may limit thin-film device performance at higher dye concentrations, resulting in LR305-PDMS LSCs being optimized for lower optical densities.…”
Section: Pdms-based Lscs/pv Assemblymentioning
confidence: 68%
See 1 more Smart Citation
“…In the presence of a black absorbing background, a maximum ISC of 3.61 mA and a maximum output power of 0.86 mW were achieved, leading to a maximum ηdev,dark background of 0.24%. The lower overall device efficiencies of LR305-PDMS LSCs with respect to previously published LR305-based thin-film LSCs tested in analogous conditions (namely, in the presence of a black absorbing background and of a black mask in front of the LSC system, without employing any reflective element at the free edges of the waveguide) [15,83] could be attributed to the poor luminophore solubility of LR305 in PDMS host matrix. As documented in previous studies [68,71,72], dye aggregation issues are responsible for generating significant luminescence quenching, which may limit thin-film device performance at higher dye concentrations, resulting in LR305-PDMS LSCs being optimized for lower optical densities.…”
Section: Pdms-based Lscs/pv Assemblymentioning
confidence: 68%
“…Similarly, a sufficiently long durability of LSC systems during operation also represents a key asset to prove the real commercial viability of this technology. In particular, two critical aspects directly affecting the lifetime of LSCs are the chemical and physical durability of the host matrix, and the photostability of the luminescent species, both addressed by designing intrinsically stable host materials [13][14][15][16][17][18] and luminophores [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A prototype doped with a perylene-based luminophore gave a η opt of 4.9% while it was shown that a damaged device undergoes full recovery of efficiency after complete thermal healing. [96]…”
Section: Polymer-based Lscsmentioning
confidence: 99%
“…Triangular [77] and even circular [78] devices have been presented. Likewise, while polymers including polymethacrylate (PMMA) and polycarbonate or glass have been the main materials used for lightguides, alternatives exist, including renewable polyester, [79] self-healing materials, [80] and even liquid LSCs have been described, [81][82][83] which could have the advantage of rapid switching of the fluorophore. The employment of flexible materials as host matrixes, such as polydimethylsiloxane (PDMS), [84][85][86] can open a new range of applications such as boat sails, tents, phone cases, and self-powered flexible electronic devices.…”
Section: Alternative Materials Locations Shapesmentioning
confidence: 99%